Analisis Pendapatan dan Motivasi Masyarakat Dalam Kegiatan Restorasi Ekosistem Pola Agroforestry di Hutan Lindung Gambut Bram Hitam Provinsi Jambi - Ulfa, Maria; Fazriyas, Fazriyas; Nurmansyah, Rahmad; Ahyauddin, Ahyauddin; Maelan, Bayu (Jurnal MeA (Media Agribisnis), 2025)
Encroachment and forest fires in Jambi Province have damaged the peat forest ecosystem. One of the peat forest areas that has experienced ecosystem damage is the Bram Hitam peat protected forest, West Tanjung Jabung Regency. In an effort to restore the peat ecosystem that has been converted by the community into oil palm plantations, planting and enrichment were carried out with the Agroforestry model. The development of an agroforestry model on peatlands is not only beneficial for restoring the ecological function of peat but is also beneficial and has economic value for communities that have joined the social forestry scheme. The purpose of this study was to analyze the income of communities that utilize agroforestry patterns in the Bram Hitam HLG. The research was conducted for 8 months from March to October 2023 at the Bram Hitam HLG, West Tanjung Jabung Regency and continued with data analysis at the Forest Management Laboratory, Faculty of Agriculture, University of Jambi. The results of the study showed that there were 6 (six) Forest Farmer Groups (KTH) that were the samples of this study. The various KTHs carry out agroforestry activities by planting different types of plants so that they produce different economic values received by farmers. income of ±21-29 million per hectare per year. The combination of types planted varies from a combination of 2 types to 4 types with the main crop being oil palm. Farmers' motivation in choosing plants and participating in ecosystem restoration activities with agroforestry is based on four aspects, namely product orientation where the types planted have the potential to be economically profitable, appropriate biophysical conditions, farmer knowledge of appropriate types and adequate allocation of time and labor in managing their land